Correction to: Endophytic colonization of tomato plants by the entomopathogenic fungus Beauveria bassiana for controlling the South American tomato pinworm, Tuta absoluta - Ana Carolina Loreti Silva; Gerson Adriano Silva; Pedro Henrique Nogueira Abib; Aline Teixeira Carolino; Richard Ian Samuels (CABI Agriculture and Bioscience)
An amendment to this paper has been published and can be accessed via the original article.